2020
DOI: 10.1111/dom.14271
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of adding sotagliflozin, a dual sodium‐glucose co‐transporter (SGLT)1 and SGLT2 inhibitor, to optimized insulin therapy in adults with type 1 diabetes and baseline body mass index ≥ 27 kg/m2

Abstract: Sotagliflozin, a dual sodium‐glucose co‐transporter (SGLT)1/SGLT2 inhibitor, is currently approved in Europe as an adjunct to optimal insulin therapy in adults with type 1 diabetes (T1D) and a body mass index (BMI) ≥ 27 kg/m2. In this post hoc analysis, efficacy at 24 weeks and safety at 52 weeks from pooled phase 3 clinical trials were evaluated in patients with baseline BMI ≥ 27 kg/m2. Sotagliflozin 200 mg and 400 mg added to insulin reduced glycated haemoglobin level and increased time in range assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…A better risk-benefit ratio associated with the use of sodiumglucose co-transporter-2 (SGLT2) inhibitors among people with type 1 diabetes has been suggested among people with a body mass index (BMI) of 27 kg/m 2 or higher, 58,59 although a recent meta-analysis has also suggested that the risk of DKA increases with excessive insulin dose reduction, higher BMI and higher insulin resistance. 60 DKA might occur among users of SGLT2 inhibitors when there is an imbalance between the amount of insulin required to halt lipolysis and the amount of available (endogenous or exogenous) insulin.…”
Section: Areas Of Uncertainties In Classical Type 1 Diabetesmentioning
confidence: 99%
“…A better risk-benefit ratio associated with the use of sodiumglucose co-transporter-2 (SGLT2) inhibitors among people with type 1 diabetes has been suggested among people with a body mass index (BMI) of 27 kg/m 2 or higher, 58,59 although a recent meta-analysis has also suggested that the risk of DKA increases with excessive insulin dose reduction, higher BMI and higher insulin resistance. 60 DKA might occur among users of SGLT2 inhibitors when there is an imbalance between the amount of insulin required to halt lipolysis and the amount of available (endogenous or exogenous) insulin.…”
Section: Areas Of Uncertainties In Classical Type 1 Diabetesmentioning
confidence: 99%
“…The risk of DKA was higher in persons randomized to sotagliflozin, and the risk of severe hypoglycemia was reduced in the sotagliflozin groups [82,83]. A post hoc analysis of the inTandem program revealed a more favorable efficacy and safety profile when sotagliflozin was used in persons with a BMI > 27 kg/m 2 compared to those with a BMI < 27 kg/m 2 [128]. Interestingly, in a recently published small study including 85 participants with not-well-controlled T1D and a younger age (18-30 years) receiving sotagliflozin 400 mg or placebo, the risk of DKA was not increased in the sotagliflozin group.…”
Section: Sglt1/2 Inhibitorsmentioning
confidence: 97%
“…Exclusion criteria: (1) Study contained inappropriate subgroup analysis or single-arm treatment; (2) the research was not a phase II or phase III clinical trial; (3) the adverse events were absent in the article; (4) the research data was not able to be extracted; (5) The latest article will be selected and reviewed when it comes to duplicates.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…SGLT2 is expressed in the kidney and could reabsorb 90% of the filtered glucose ( 2 ). Since insulin therapy alone cannot achieve adequate control of blood sugar in most DM patients ( 3 ), sotagliflozin, a dual inhibitor that targets SGLT1 and SGLT2 ( 4 ), was currently approved in Europe as the best auxiliary drug with insulin for the treatment of adults with DM and a body mass index (BMI) of ≥ 27 kg/m 2 ( 5 ). The primary metabolic effect of sotagliflozin is mediated by SGLT2-inhibition in the kidney, while some additional postprandial glucose control may be mediated by inhibition of SGLT1 in the intestine ( 3 , 4 , 6 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation